Litigation Risk, Intermediation, and the Underpricing of Initial Public Offerings - Hughes, Patricia J.; Thakor, Anjan V. (Review of Financial Studies, 1992)
We formally examine the role of litigation risk in initial public offering (IPO) pricing. The underwriter's pricing decision trades off current revenue against expected future litigation costs, both of which are increasing in the IPO price. Given a time-consistency constraint and rational expectations on the part of investors, however, the "standard" litigation risk argument does not lead to equilibrium underpricing. We develop a richer model that provides sufficient conditions under which there is equilibrium underpricing. The issuer's choice of employing an underwriter versus floating the IPO on its own is examined, and various testable implications of the model are developed. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.